DEVELOPING STUDENTS' CREATIVE THINKING SKILLS IN THE PROCESS OF TRANSFORMING HIGHER PEDAGOGICAL EDUCATION - Tursunova Shahzoda Baxromovna (Bright Mind Publishing, 2025)
This article discusses numerous challenges faced by higher pedagogical education that require new teaching approaches. One of the main directions is the development of creative thinking skills in students. Creative thinking not only helps future educators effectively solve emerging problems but also facilitates the implementation of innovative teaching methods that promote deeper and more sustainable knowledge acquisition.
Keywords: Creativity, creative thinking, innovative thinking, qualification, skill, knowledge, competence, component, interactive, integration.